2014
DOI: 10.1890/es13-00290.1
|View full text |Cite
|
Sign up to set email alerts
|

Disparate responses of above‐ and belowground properties to soil disturbance by an invasive mammal

Abstract: Abstract. Introduced mammalian herbivores can negatively affect ecosystem structure and function if they introduce a novel disturbance to an ecosystem. For example, belowground foraging herbivores that bioturbate the soil, may alter process rates and community composition in ecosystems that lack native belowground mammalian foragers. Wild boar (Sus scrofa) disturb the soil system and plant community via their rooting behavior in their native range. Given their size and the numbers in their populations, this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Los Alerces, Lago Puelo, Nahuel Huapi, Lanín, Lihue-Calel, Sierra de las Quijadas, El Palmar, and Reserva El Leoncito) (Novillo and Ojeda, 2008;Schiaffini and Vila, 2012). In Patagonia, its presence has been confirmed by direct observation and by the presence of feces and rooted patches produced as a consequence of the feeding habit (Barrios-Garcia et al, 2014).…”
Section: Introductionmentioning
confidence: 87%
“…Los Alerces, Lago Puelo, Nahuel Huapi, Lanín, Lihue-Calel, Sierra de las Quijadas, El Palmar, and Reserva El Leoncito) (Novillo and Ojeda, 2008;Schiaffini and Vila, 2012). In Patagonia, its presence has been confirmed by direct observation and by the presence of feces and rooted patches produced as a consequence of the feeding habit (Barrios-Garcia et al, 2014).…”
Section: Introductionmentioning
confidence: 87%
“…Whether this scales up to landscape-level effects is unclear. Short-term exclusion studies on invasive boars and feral pigs showed weak effects on soil properties [48,49], but studies of longer duration showed strong effects on nutrient cycling and uptake by plants [50] and on soil microarthropod populations [51]. In fact, in European ecosystems in which they occur naturally, boars significantly affect soil properties [52] and fauna [53,54].…”
Section: (B) Digging and Burrowing Vertebratesmentioning
confidence: 99%
“…2003 ; Garzón-Machado et al . 2010 , Barrios-Garcia et al . 2014 ); (vi) species distribution models (SDMs) to determine environmental constraints and potentially favourable areas, possible impacts of climate change and of other anthropogenic alterations ( Costa et al 2012 , 2013 a ; Marcer et al .…”
Section: Introductionmentioning
confidence: 99%